La lúdica en el proceso de lecto-escritura en el sexto grado. - Chicaiza Tigasi, Liliana América (2021)
The present project was focused on students’ literacy deficiencies, that represents a recurring problem in educational institutions and it contributes a limitation to meaningful learning, since through reading and writing might express ideas and thoughts, as well as acquiring information using written language. The objective was to analyze the playful strategies as a means to enhance literacy in sixth grade students from “Saraugsha” Intercultural Community Educational Unit, considering that playfulness offers a particular contribution since pedagogical approach, contributing in the development of learning experiences that promote freedom and enjoyment. For this reason, a quantitative approach methodology was applied, combined the feasible project modality, whose structure is composed by elaboration and development of a viable proposal or operating model. This research was conducted through applied research in order to achieve the comprehensive level on that. The empirical methods used were observation and survey. It was so important the participation of principal authority, 18 teachers and 11 students. The main results of this research have made it possible to show that through playful strategies, spaces and experiences may be fostered improving the motivation, interest and participation of the learner, which significantly helps the development of reading and writing skills.